A Case-Based Review of Cerebral Venous Infarcts With Perfusion Imaging and Comparison to Arterial Ischemic Stroke - Li, Anna Y.; Tong, Elizabeth; Yedavalli, Vivek S. (Frontiers in Radiology, 2021)
Cerebral venous thrombosis (CVT) and cerebral venous infarcts (CVI) are diagnostic dilemmas secondary to their rarity, non-specific symptomatology at presentation, and variable imaging features. Despite its relatively infrequence, CVT is particularly prevalent in the younger adult population and is a potentially life-threatening disease with devastating neurological complications if not addressed in a timely manner. However, when treated promptly, CVT has the potential for a more reversible course and favorable prognosis than arterial ischemic strokes (AIS). The pathophysiology of CVI is distinct from that of AIS and is closely related to its potentially reversible nature. Familiarity with the conventional and variant venous anatomy, as well as the temporal evolution of imaging findings, is crucial in establishing diagnostic confidence. The use of MR perfusion imaging (MRP) and arterial spin-labeling (ASL) can potentially aid in the diagnosis of CVT/CVI via characterization of cerebral blood flow. The presence and extent of a cerebral perfusion deficit on either CT or MRI may play a role in clinical outcomes for patients with CVT, although future larger studies must be performed. This review presents a case-based overview focusing on the classic imaging characteristics of CVT and CVI in conjunction with bolus MRP and ASL findings in the adult population.